Kant's School of Morals: The Challenge of Radical Evil and the Need for Moral Education in Religion within the Limits of Reason Alone - Goski, Joseph Wyllie (Université d'Ottawa / University of Ottawa, 2014)
My aim in this thesis is to demonstrate that common interpretations of Kant’s theory of respect do not account for the motivation a subject feels to follow the moral law. A large number of interpreters focus on Kant’s early ethical works—such as the Grounding and the Critique of Practical Reason—to justify how the moral law alone motivates a subject to act rightly. However, by the time he published Religion within the Limits of Reason Alone, Kant had discovered the problem of radical evil—the fact that people tend to feel more motivated by the inclinations than by the moral law. Kant’s solution to this challenge comes in the form of moral education: the contingent practices of historical institutions (factors that are extraneous to the moral law) are required to learn respect for the law. By the end of the Religion, it will be asked whether duty for duty’s sake is ever achieved.
Keywords: Philosophy; Immanuel Kant; Ethics; David Hume; Religion; Enlightenment; 18th century